The Factors Affecting the Risk of Falls Among Elderly in the Working Area of Motoboi Kecil Public Health Center - Tumurang, Marjes (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2025)
In the course of their lives, the elderly will experience all the limitations associated to health problems. Biologically, the physical endurance of the elderly population is weakening. This can be caused by a decrease in the structure and function of cells, tissues, and organ systems of the elderly body. It can be proven that the elderly group suffers more from diseases that cause a decrease in the ability to carry out activities compared to people who are still easy. Diseases and problems that are often faced by the elderly are easy to fall. Falling is a condition in which a person falls with or without being witnessed by others, accidentally or planned, with the direction of falling to the floor, with or without injuring himself. This study aims to determine factors affecting the risk of falling in the elderly at UPTD Puskesmas Motoboi Kecil. This study used a cross sectional design. The number of samples in this study were 35 respondents. Data analysis using the Chi-Square Test. 1. result showed that there was a correlation between the factor of visual impairment and the use of walking aids and the risk of falling on the elderly at the UPTD Puskesmas Motoboi Kecil with a P Value = 0.000 or <P = 0.05. 2. result showed that there was a correlation between visual impairment and environmental factors and the risk of falling on the elderly at the UPTD Puskesmas Motoboi Kecil with a P value = 0.019 or <P = 0.05. After the Chi- Square test was carried out, it was found that there was a correlation between the walking aid factor and the environmental factors at risk of falling on the elderly at the UPTD Puskesmas Motoboi Kecil with a P value = 0.002 or <P = 0.05.